Interprofessional collaboration in Paediatric Obstructive Sleep Apnoea (POSA) treatment: Assessment of professional orientation levels amongst otolaryngologists in South India - Bhagyalakshmi Avinash; M.B. Bharathi; Chandrashekar Channanayak; Ramprasad Vasthare; Y.R. Arron Lim; Prajna P. Nayak (Elsevier, 2024)
Objective: The primary goal was to assess the knowledge, attitude and practice among otorhinolaryngologists regarding orthodontic intervention for Paediatric Obstructive Sleep Apnoea (POSA). Methods: An online survey was conducted by sending an email invitation to members of The Association of Otorhinolaryngologists of Karnataka, India. A total of 141 otorhinolaryngologists participated in the survey. Results: Most of the participants (70.2%) agreed that orthodontic interventions help in opening up the airway, but very few knew about its application in nasal obstruction management. Conclusion: Otorhinolaryngologists are aware of dental effects of POSA and they believe that an interprofessional team is essential for its management. This learning can also be used to initiate interprofessional collaborations and academic and curricular improvisations for enhanced health outcomes.